2016
DOI: 10.1155/2016/8791629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Immunologic Profiles in Incomplete Lupus Erythematosus and Improvement with Hydroxychloroquine Treatment

Abstract: Objective. The study goals were to evaluate performance of SLE classification criteria, to define patients with incomplete lupus erythematosus (ILE), and to probe for features in these patients that might be useful as indicators of disease status and hydroxychloroquine response. Methods. Patients with ILE (N = 70) and SLE (N = 32) defined by the 1997 American College of Rheumatology criteria were reclassified using the 2012 Systemic Lupus International Collaborating Clinics criteria. Disease activity, patient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
22
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 30 publications
(39 reference statements)
6
22
1
3
Order By: Relevance
“…Most publications on iSLE are based on patients with clinical features of SLE who do not fulfill ACR criteria (3), and only some studies use the SLICC criteria. Table shows an overview of these studies .…”
Section: Introductionmentioning
confidence: 99%
“…Most publications on iSLE are based on patients with clinical features of SLE who do not fulfill ACR criteria (3), and only some studies use the SLICC criteria. Table shows an overview of these studies .…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, the features of SLE can be present over several years before formal classification is possible. This has given rise to the term incomplete lupus erythematosus (ILE), which may be used to refer to individuals with clinical or serologic features of lupus who are progressing to incident SLE, as well as individuals who never develop the requisite number of criteria for formal classification ().…”
Section: Introductionmentioning
confidence: 99%
“…However, HCQ has not been rigorously tested in patients with ILE. While a recent study showed that ILE patients taking HCQ had lower expression levels of type I interferon‐inducible genes than those not taking the drug, the long‐term clinical benefit of this medication is unknown ().…”
Section: Introductionmentioning
confidence: 99%
“…2). Следует подчеркнуть, что стандартная терапия ИВРЗ базисными противовоспалительными препаратами (БПВП), в первую очередь ГК и гидроксихлорохином (ГХ), подавляет экспрессию ISGs при СШ [82], первичном антифосфолипидном синдроме [75], подострой кожной волчанке [83], «неполной» красной волчанке [84]. В связи с этим представляют интерес данные, касающиеся дефектов клеточной регуляции синтеза ИФНα при ИВРЗ, которые потенциально могут рассматриваться в контексте механизмов действия БПВП [22].…”
unclassified